Analysis of Pancasila Values-Based on Character Building to Develop Perspective of Elementary School-Age Children - Kharisma Romadhon; Shaleh Shaleh; Sri Atin; Noor Alfi Fajriyani; Muftahatus Sa'adah; Irfan Irfan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In terms of child development, this paper explains the character building that aligns with Pancasila's values. The research in this paper aims to analyze character building in accordance with Pancasila values from the perspective of the development of elementary school-aged children. The research uses a qualitative descriptive strategy. The steps are observation, interviews, and documentation techniques as an approach to data collection. In the observation process, the researcher conducted observations in the classroom. The interviewed informants were the school principal and class teacher. The information was collected through published literature. The data that have been found were triangulated and tested for validity to validate the findings. The research results indicate that from a child development perspective, character development can be divided into three domains, namely cognitive development, linguistic development, and social and emotional development. Learning environment that encourages students' original thinking can be created through cognitive development. To help children develop their language skills, educators should teach them consistently how to speak politely in formal and informal languages. Students are expected to take responsibility for themselves, others, and their academic commitments as part of their social and emotional growth.